EXPLORING HOME ENVIRONMENT AND SELF-DIRECTED LEARNING EFFICACY OF MULTILINGUAL AND NON-MULTILINGUAL STUDENTS - Ayik, Bilgehan; Wahidi, Sahar (International Online Journal of Education and Teaching, 2025)
The impact of school closures during the COVID-19 pandemic was disproportionate on multilingual learners (MLs) as compared to non-MLs. Utilizing the PISA 2022 dataset and focusing on differences between MLs and non-MLs, this study explores the relationships between family support for self-directed learning (SDL), feelings about learning at home, and SDL self-efficacy (SDL-SE) in the US. First, measurement invariance was examined to determine possible differences due to group membership. Next, we explored the mediating influence of feelings about learning at home on the relationship between family support for SDL and SDL-SE and examined differences in these relationships between groups. Findings revealed that MLs and non-MLs had similar levels of SDL-SE; however, ML students had a stronger direct relationship from family support for SDL to SDL-SE, whereas non-ML students had a stronger indirect effect through feelings about learning from home. Implications regarding research, practice, and policy are discussed.